1973
DOI: 10.1017/s0022029900014515
|View full text |Cite
|
Sign up to set email alerts
|

Friction between the teat and teatcup liner during milking

Abstract: Four studies are described of the role of friction in maintaining the teatcup stable on the teat. Measurements of the coefficient of friction between teats and pieces of liners, in which most values for the coefficient fell between 0-5 and 1-0, indicated that friction between skin and rubber-like materials was consistent with the general frictional behaviour of elastic solids. Studies during milking showed that the sudden restriction of milk flow that normally occurs near the end of milking is accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…Nevertheless, a too low vacuum could be counterproductive and could result in a longer milking time and a higher frequency of the teat cups slipping and falling off (Spencer and Rogers 1991) that could be deleterious for udder health. On the contrary, higher vacuum shortened milking process by increasing milk flow in cluster and tubes but can induce injury (petechial hemorrhages, teat sphincter eversion…) and even reduce milk flow at the end of milking because of teat tissue edema (Hamann and Mein 1990) and liner climbing that can also increase stripping milk by closing the cricoïd ring (Mein et al 1973). …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a too low vacuum could be counterproductive and could result in a longer milking time and a higher frequency of the teat cups slipping and falling off (Spencer and Rogers 1991) that could be deleterious for udder health. On the contrary, higher vacuum shortened milking process by increasing milk flow in cluster and tubes but can induce injury (petechial hemorrhages, teat sphincter eversion…) and even reduce milk flow at the end of milking because of teat tissue edema (Hamann and Mein 1990) and liner climbing that can also increase stripping milk by closing the cricoïd ring (Mein et al 1973). …”
Section: Introductionmentioning
confidence: 99%
“…Forces generated by the liner vacuum act to pull the teat deeper into the liner, and gravity acts to pull the teatcup off the teat. To maintain a stable position on the teat, the teatcup depends on frictional force between the teat and the liner wall (Mein et al 1973).…”
mentioning
confidence: 99%
“…This results in a pressure gradient that presses the teat against the liner. Because of increased friction, it requires a greater force to pull the teatcup off the teat when the MPC vacuum is high compared with lower MPC vacuum, and the risk of liner slips during peak flow rate is reduced (Mein et al 1973).…”
mentioning
confidence: 99%
“…Recently Mein et al (1970) reported that frictional properties of liners appeared to have an important and progressively increasing influence on the depth of penetration of the teat in the liner during the course of a milking. Mein et al (1973) further reported that during the period of peak milk flowrate, the major source of friction maintaining the teat cup stable on the teat is the large area of contact between the teat and liner barrel.…”
Section: Discussionmentioning
confidence: 99%